360° approach to the patient with mite allergy: from scientific evidence to clinical practice - Nieto-García, Antonio; Abel-Fernández, Eva; Nieto-Cid, María; Pineda de la Losa, Fernando (Frontiers in Allergy, 2024)
In the recent years, several important advances have been made in the diagnosis of allergy using molecular techniques. The aetiological diagnosis of allergy using molecular components of allergens allows a more precise definition of the patient's IgE repertoire. Precision medicine is a structural model aimed at personalising healthcare and places the patient at the centre of the specialist's decision-making process. To this end, an accurate characterisation of the external exposome at a molecular level and their putative role as clinically relevant allergens is essential to elucidate the phenotypic diversity of atopic disease, with a view to personalising diagnosis and therapy. It has been proposed a decision algorithm, the Top-Down approach, where the clinical history is set first and is followed by the use of skin tests or specific IgE techniques, which facilitates the clinicians to make decisions. The therapeutic intervention driven by the standard diagnostic approach, but supported by these innovative tools, can lead to a better phenotyping of highly complex patients, and a more appropriate prescription of AIT. To this end, the allergen extracts used for diagnosis require to be of proven quality and contain the most relevant allergens. Likewise, allergen vaccines must gather efficacy, safety, duration, and patient compliance, hence the demand for new vaccines to overcome these drawbacks.